Islam and Citizenship Education - Aslan, Ednan (Springer, 2015)
The scholarly contributors to this volume investigate various means to stimulate and facilitate reflection on new social relations while clarifying the contradictions between religious and social affiliation from different perspectives and experiences. They explore hindrances whose removal could enable Muslim children and youth to pursue equal participation in political and social life, and the ways that education could facilitate this process.